Developing effective pedagogical approaches in science outreach programs for young children - Howitt, C.; Blake, E.; Rennie, Leonie (2017)
© Springer International Publishing AG 2017. Recognition of the importance of providing science-related experiences for young children has resulted in increased numbers of outreach programs aimed at a preschool audience. Early meaningful experiences of science have been found to promote children’s interest in science and enhance their self-belief that they can be effective science learners. However, ensuring that outreach programs fulfill their potential depends largely on the pedagogical approaches of the informal educators who deliver the program. Understanding how young children learn and valuing the range of knowledge and experience they bring provides a context in which their formative ideas about science can be shaped. In this chapter we draw upon our research into one outreach program with 3- and 4-year-old children where we worked with informal science educators to promote a positive environment that encouraged learning through play. We found that effective pedagogy involved active participation by the educator throughout the program. This role involves, firstly, emotional support, followed by modelling and encouraging exploration by the children, and then questioning. Through this process informal science educators can develop science conversations with children to extend their current knowledge and ideas. Our research emphasized that informal science educators must thoroughly understand the purpose and potential of their outreach program as a whole and that it is more than offering young children a variety of interesting activities.